A Study of Science Process Skills on Simple Pendulum Materials - Samijo Samijo; Dinda Desma Romadona (Cahaya Ilmu Cendekia Publisher, 2023)
Research Objectives: The objective of this study was to describe students' science process skills in simple pendulum material. Methodology: This research method is a mixed research method with a sequential explanatory research design. This research involved 100 students of Al-Falah Jambi Islamic High School. The instruments used were KPS observation sheets with 16 indicators and interview sheets which were analyzed statistically descriptively then analyzed qualitatively to strengthen the quantitative data. Main Findings: The results of the student KPS indicator were very good, namely on the observation indicator with a percentage of 71% of 100 students, while the results on the KPS indicator with a percentage of 66%. of 100 students namely experimenting skills. The lowest result is the presence of predictive indicators that identify variables, and make hypotheses with a percentage of 45%, 66% and 44%. These results indicate that students have sufficiently mastered several KPS in this simple pendulum material. Novelty/Original Research: How important it is for an educator to be able to improve students' science process skills so that they not only develop cognitive aspects, but also psychomotor aspects, according to the goals of education.